PEMERIKSAAN FRAUD DALAM AKUNTANSI FORENSIK DAN AUDIT INVESTIGATIF - Sayyid, Annisa (Al-Banjari : Jurnal Ilmiah Ilmu-Ilmu Keislaman, 2014)
The History of world bussiness is full of ethics violation cases and financial scandals. Public can even see clearly the various economic crimes such as corruption, financial engineering and money laundering. These issues are always interesting since it involves tricks in information presentation which indicates a fraud. The application of forensic accounting and investigative audits is a solution to the anxiety of financial world. Forensic accounting and investigative audits in its simplest form is a blend between the disciplines of accounting, auditing and law. Forensic accounting is the use of accounting skills combined with the ability to solve a problem or alleged fraud. The investigative audit is an attempt to prove a mistake in accordance with the provisions of applicable law.